ANALYSIS METALS Fe AND Mn IN SEAGRASS ENHALUS ACOROIDES IN THE WATERS PASARWAJO BUTON - Sabaniah Indjar Gama; Nursiah La Nafie; Seniwati Dali (Marina Chimica Acta, 2015)
The research aims to identify ferrous metals and manganese in seagrasses Enhalus acoroides. The sample used was obtained from the water pasarwajo buton. The sample was extracted, then the metal was analyzed using AAS. Metal concentrations (ppm) are Fe (143.667 mg / kg) and Mn (46.67 mg / kg), respectively. Metal content obtained below the maximum limit and seagrass Enhalus acoraides can be used as a bio-indicator of the presence of heavy metals